Air-Exposure-Driven Color and Optical Variations in Hydroxyapatite Extracted from Fish Scales - Okur, H. Esma (My University, 2025)
The disposal of fish scales as waste presents an environmental challenge and an untapped opportunity for resource recovery. In this study, hydroxyapatite (HAp) was extracted from European seabass (Dicentrarchus labrax) scales to explore how air exposure during calcination affects its optical and surface properties. HAp powders were prepared under two distinct calcination conditions: fully exposed to air (producing white powder) and partially shielded from air (resulting in gray powder). Rietveld refinement of X-ray powder diffraction (XRPD) data confirms that both powders crystallize in the hexagonal HAp structure, with a minor Mg-whitlockite impurity. Despite these differences in air exposure, the bulk structure of the HAp remains unchanged. The color variations are linked to surface oxidation, as subsurface layers in the partially shielded scales retains a grayish tone while the exposed surfaces turn completely white. Scanning electron microscopy reveals subtle differences in particle morphology: the white powder had a smoother surface compared to the slightly rougher gray powder. Fourier transform infrared spectra confirms the presence of characteristic phosphate and hydroxyl groups in both powders, indicating that the core chemical structure of HAp is intact in both cases. The Ca/P ratios—1.504(7) for the white powder and 1.505(7) for the gray powder obtained from the Rietveld analysis—further supports the stoichiometric integrity of the material. UV-Vis spectroscopy reveals direct bandgap values of 3.99 eV for the white powder and 3.87 eV for the gray powder. These bandgap values, which are lower than those typically reported for defect-free HAp (5–6 eV), suggest that the optical differences between the powders are driven by surface effects, such as oxygen vacancies or trace impurities. This study highlights how calcination conditions, particularly air exposure, influence surface properties and optical behavior, paving the way for potential applications of fish-scale-derived HAp in electronic and optical materials.
Keywords: Hydroxyapatite; Band gap; Rietveld refinement; Fish scales; Air exposure